Eligibility of Village Head Elections in the Midst of the Covid-19 Pandemic in the Perspective of Human Rights in Sidoarjo Regency - Iqbal Purwo Nugroho; Rifqi Ridlo Phahlevy (Indonesian Journal of Cultural and Community Development, 2022)
The Village Head Election is a form of village-level democracy, the Village Head Election in 2020 is very important to note its implementation by implementing the Health protocol. In particular, the village head election in Sidoarjo which was held in the midst of the Covid 19 Pandemic this year was not only an implementation of political rights, but also included the community's right to life which was threatened. The purpose of this study is to analyze the implementation of the Pilkades during the COVID-19 pandemic in villages in the Sidoarjo district from the perspective of Human Rights and also to analyze the pattern of implementation of the Pilkades during the pandemic in Sidoarjo district villages according to human rights. This type of research is sociological juridical, where this research serves to see the law in a real sense and also to see how the law works in society. From the results of the study, it was found that from the four samples of villages that had implemented health protocols in the Pilkades on December 20, 2020, so that the application of a health protocol that guaranteed political rights and the right to life simultaneously could be used as a pattern for implementing the Pilkades in the perspective of human rights in the future which would not only be applied to the Pilkades. but also in the E Voting Pilkades.